Influence of working out at home on the expansion of cardiovascular disease risk factors - Tsos, Anatolii; Sushchenko, L.; Bielikova, Natalia; Indyka, Svitlana (My University, 2016)
Currently, the concept of correction of cardiovascular disease risk factors is a generally accepted strategy for cardiological pathology prevention. Adequate physical activity serves as a generating factor in prevention or minimization of complications after acute myocardial infarction. Patients who irregularly attend specially organized classes in rehabilitation centers, because of lack of time or otherwise, have an alternative, i.e., selforganized physical activity at home. The purpose of the research was introduction of the author physical training at home for people who had heart attack for the purpose of secondary prevention of complications and for rehabilitation. Two groups were formed by random sampling: 1st - the main group (used the author program of physical training at home) and the 2nd - the group of comparison (proceeded with the treatment (course of physical training) in a specialized rehabilitation department). Each group consisted of 30 males who were in a phase of recovery after acute myocardial infarction. Methodology of the author program is based on the principles of complexity and individualization, and included strict dosage and gradual increase of physical activity by amplitude, intensity and complexity of exercises. It differs from the methodology of the rehabilitation center’s program in duration of classes and their strict division; in orientation of special exercises of dynamic nature on moto-visceral reflexes that innervate the heart and stimulate central and peripheral mechanisms of blood circulation; in daily monitoring. The educational part of the program included attendance of School “Step to Healthy Heart”, distance learning with online patients’ support site. By estimation of the major risk factors for cardiovascular disease among patients of both groups at the beginning of the research it was found out that obesity, abdominal obesity, high blood pressure, high cholesterol, smoking are the most common risk factors among the above mentioned two groups. As a result statistically significant weight loss, cholesterol reduction and systolic blood pressure loss were recorded among the patients of the main group. Significant and steady reductions of the listed above indicators emphasize adequacy of selected physical activity at home. In the group of comparison such changes are observed only at the beginning of the study.
Keywords: myocardial infarction; independent study; risk factors; physical education